Primary progressive aphasia and motor neuron disease: A review - Aiello, Edoardo Nicolò; Feroldi, Sarah; De Luca, Giulia; Guidotti, Lucilla; Arrigoni, Eleonora; Appollonio, Ildebrando; Solca, Federica; Carelli, Laura; Poletti, Barbara; Verde, Federico; Silani, Vincenzo; Ticozzi, Nicola (Frontiers in Aging Neuroscience, 2022)
Background. This study aims at reviewing, within the framework of motor neuron disease-frontotemporal degeneration (MND-FTD)-spectrum disorders, evidence on the co-occurrence between primary progressive aphasia (PPA) and MND in order to profile such a complex at pathological, genetic and clinical levels. Methods. This review was pre-registered (osf.io/ds8m4) and performed in accordance with the 2020 PRISMA guidelines. Case reports/series and group studies were included if addressing (1) progressive non-fluent aphasia (PNFA) or semantic dementia (SD) with MND or (2) MND patients with co-morbid PNFA/SD. Results. Out of 546 initial records, 56 studies were included. As to case reports/series (N=35), which included 61 PPA-MND patients, the following findings yielded: 1) PNFA is more frequent than SD in PPA-MND; 2) in PPA-MND, the most prevalent motor phenotypes are amyotrophic lateral sclerosis and predominant-upper MND, with bulbar involvement being ubiquitous; 3) extrapyramidal features are moderately frequent in PPA-MND; 4) PPA-MND patients usually display frontotemporal, left-greater-than-right involvement; 5) TDP-43-B is the typical pathological substrate of PPA-MND; 6) TBK1 mutations represent the most frequent genetic risk factors for PPA-MND. As to group studies, including 121 patients, proportional meta-analytic procedures revealed that: 1) the lifetime prevalence of MND in PPA is 6%; 2) PPA occurs in 19% of patients with co-morbid MND and FTD; 3) MND is more frequent in PNFA (10%) than in SD patients (3%). Discussion. Insights herewith delivered into the clinical, neuropathological and genetic features of PPA-MND patients prompt further investigations aimed at improving clinical practice within the MND-FTD spectrum.